Manajemen Berbasis Sekolah Di Smk Muhammadiyah 2 Ngawi (Studi Perkembangan Tahun 2012- 2015) - SUMADI, ADI, Prof. Dr. Bambang Sumardjoko, Dr. Mutohharun Jinan, M.Ag (2016)
The purpose of this study is to determine the development of SMK Muhammadiyah 2 Ngawi, the opinions of the society, the leader of the community, the stakeholder of its existence, and the management which is applied, and also the management which the teachers and the officers need. This study used qualitative approach, in which the result is descriptive data. The study tried to reveal the facts of its natural condition as the direct source with instruments from the researcher. The subject of the information is the principal, the vice principal (of curriculum, students field, public relation, infrastructure), teachers, officers, environment community which consists of student's parents, the leaders of the community, and work partners of SMK Muhammadiyah 2 Ngawi. The results of the study have shown that (1) The history of SMK Muhammadiyah has three periods, they are pioneering, development, and progress periods (2) According to some leaders of community and environment community, the existence of SMK Muhammadiyah 2 Ngawi is necessary. (3) The implementationof school based management in SMK Muhammadiyah 2 Ngawi has run well, it was proved by: (a) There are planning, organizing, implementing, and controlling in every program. (b) There is a good cooperation between the school community, school environment, industry and companies. The school transparency has run well in arranging program and school finance is planned by involving the school community, the student's parents, the leaders of the community, and business world in arranging, planning, and managing the resources in student's parents meeting which initiated by the committee. (d) School accountability has run well as the implementation and the administration of physic or non physic program could be responsible. School makes responsibility mechanism through reporting which is reported in meeting with the school community, school committee, foundation, and the government. (4) The implementation of management in transparency and accountability in SMK Muhammadiyah 2 Ngawi has run well, however the displaying of RKS, RAPBS, and finance report should be put on the place where the community, school committee, and the students could see. Keywords: Management, School